Avaliação da tecnologia assistiva na sala de recursos multifuncionais : estudo de caso em Fortaleza – Ceará - Rodrigues, Maria Euzimar Nunes (2013)
Assistive technology is a knowledge area that includes products, strategies, methodologies, resources, practices and services that aid disabled people to acquire autonomy. Thus, it makes possible the enlargement of their functional abilities related to the execution and participation in different activities, promoting accessibility and consequent improvement of quality of life and social inclusion. Assistive technology is discussed by several authors. At the educational area, it conquered a relevant space, showing several benefits to disabled students that, independently of their sensorial, intellectual or physical limitations, can have access to knowledge. The main purpose of the current research was to accomplish an investigation about the use of assistive technology at multifunctional resource classrooms of municipal schools in Fortaleza- CE, as well as their contribution to disabled students. Specifically, this study aimed: describe the scenery of multifunctional resource classrooms of the municipal educational system in Fortaleza-CE, with emphasis on their infrastructure; delineate the profile of the teachers' formation for the use of assistive technology; analyze the teachers' pedagogic practices of the multifunctional resource classrooms concerning the use of assistive technology; discover the contributions of the use of the low cost assistive technology for the teachers of multifunctional resource classrooms to disabled students concerning the process of inclusive education; analyze the relationship of diagnostic and formative evaluation with assistive technology. Thus, for this investigation, it took place a study found in the perspective of inclusive education focusing the use of assistive technology for disabled students, evaluating their use for the teachers of multifunctional resource classrooms, based on studies accomplished by Bersch (2007), GalvãoFilho (2009), Kensky (2003), Raiça (2008), Manzini (2005). At this investigation, it was used the qualitative/quantitative research, understood as essential for the aimed objectives, found in an exploratory investigation undertaken at schools of the municipal educational system in Fortaleza-CE. The results revealed that assistive technology offers services, resources and strategies to the needs of disabled students, changing the school context significantly, favoring the inclusion indeed, if used in an appropriate way to those students' needs. However, assistive technology itself is not a warranty for a full process of learning.